Non-Cognitive Diagnostic Assessment of Class 7 Islamic Education Learning at Junior High School - Syi'bul Huda, Ali Anhar; Khairina, Gusti Putri (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
The research was conducted to determine the implementation of non-cognitive diagnostic assessment of the ability to read and write hijaiyah letters and write Al-Quran verses, the results of non-cognitive diagnostic assessment of the ability to write hijaiyah letters and Al-Quran verses of 7th-grade students at SMPN 3 Lembang. The research design used a qualitative approach with a field study method of 305 students in grades 7D-7K with descriptive quantitative data analysis. The results revealed that in conducting the assessment, the teacher compiled an assessment rubric and used the percentage formula to measure the ability to read and write the Quran. Then, in general, the ability to read the Al-Quran of students in grades 7D-7K is categorized as fluent in as many as 148 students (49%), and their ability to write hijaiyah letters and Al-Quran verses is categorized as proficient in as many as 225 students (74%). This study concludes that no students can read the Quran and cannot write hijaiyah letters and Quranic verses. The implication of this study can be used as a basis for making non-cognitive diagnostic assessment instruments of the ability to read and write the Quran for learning preparation within the framework of an independent learning curriculum at all levels, specifically at the junior high school level in PAI subjects.